The problem of form in objects under redevelopment (on the basis of Bytom Market Square redevelopment design) = Problem formy w obiektach przebudowywanych (na przykładzie projektu realizacyjnego przebudowy bytomskiego rynku) - Maryńczuk, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author believes that if a designer has performed many design or research works entailing solutions to various problems, it is recommendable to consider and become aware of previously used methods whose application might have been unwitting or instinctive.
Keywords: renowacja; przestrzeń publiczna; projektowanie koncepcyjne; metoda KJK; kompozycja form; renovation; public space; conceptual design; design; method CQC; composition of forms